Prognostic Impact of KRAS Mutation Subtypes in 677 Patients with Metastatic Lung Adenocarcinomas. Issue 3 (March 2015) - Yu, Helena A.; Sima, Camelia S.; Shen, Ronglai; Kass, Samantha; Gainor, Justin; Shaw, Alice; Hames, Megan; Iams, Wade; Aston, Jonathan; Lovly, Christine M.; Horn, Leora; Lydon, Christine; et al.
Abstract : Background: We previously demonstrated that patients with metastatic KRAS mutant lung cancers have a shorter survival compared with patients with KRAS wild-type cancers. Recent reports have suggested different clinical outcomes and distinct activated signaling pathways depending on KRAS mutation subtype. To better understand the impact of KRAS mutation subtype, we analyzed data from 677 patients with KRAS mutant metastatic lung cancer. Methods: We reviewed all patients with metastatic or recurrent lung cancers found to have KRAS mutations over a 6-year time period. We evaluated the associations among KRAS mutation type, clinical factors, and overall survival in univariate and multivariate analyses. Any significant findings were validated in an external multi-institution patient dataset. Results: Among 677 patients with KRAS mutant lung cancers (53 at codon 13, 624 at codon 12), there was no difference in overall survival for patients when comparing KRAS transition versus transversion mutations ( p = 0.99), smoking status ( p = 0.33), or when comparing specific amino acid substitutions ( p = 0.20). In our dataset, patients with KRAS codon 13 mutant tumors ( n = 53) had shorter overall survival compared with patients with codon 12 mutant tumors ( n = 624) (1.1 versus 1.3 years, respectively; p = 0.009), and the findings were confirmed in a multivariate Cox model controlling for age, sex, and smoking status (hazard ratio: 1.52, 95% confidence interval: 1.11–2.08; p = 0.008). In an independent validation set of tumors from 682 patients with stage IV KRAS mutant lung cancers, there was no difference in survival between patients with KRAS codon 13 versus codon 12 mutations (1.0 versus 1.1 years, respectively; p = 0.41). Conclusions: Among individuals with KRAS mutant metastatic lung cancers treated with conventional therapy, there are no apparent differences in outcome based on KRAS mutation subtype.